Creating sports communities to foster healthy habits and prevent loneliness: developing a mobile application to connect people to be active - leveraging low-code solutions to promote community building - Soloviovi, Veronika (2023)
In recent years the number of people experiencing loneliness has been rising, even though society has never been more digitally connected. This work develops a digital solution to address the problem by targeting the consequences. First, a description of OutSystems, a low code development platform, is presented. Followed by research to ideate a solution that addresses the physical and mental health of individuals. This effort resulted in the development of the Connactive application - a digital platform for organizing and participating in sports events and activities to support healthier and connected communities and thus create social impact. This work project is the result of a group research in which, in addition to the presented scope of activities, a detailed analysis and elaboration of idea development, validation and design has been performed.